Compression Molding Characteristics of Seed Cotton and Damage from Cottonseed Crushing - Xuewen Fu; Ximei Wei; Meng Wang; Hongwen Zhang; Lei Wang; Jun Wang; Yuanzhao Zheng (Agriculture, 2024)
This study investigated the impact of compression molding parameters on the post-molding characteristics of machine-harvested seed cotton and aimed to determine the optimal compression molding parameters. The closed compression test of seed cotton and force analysis on a single cottonseed clarified the boundary conditions for cottonseed crushing and the relationship between crushing rate and compressive force. A seed cotton compression test bench facilitated single-factor and four-factor, three-level quadratic regression orthogonal experiments, varying the moisture content, initial density, compression force, and holding time. Variance analysis revealed each factor’s influence on the dimensional stability coefficient. Utilizing Design Expert 13.0.5, the optimal compression molding parameter ranges were identified: 6–11.7% moisture content, 47.87–74.84 kg/m3 initial density, 3–5.32 kN compression force, and 50–239.75 s holding time. Software predictions within this range indicated an optimal cottonseed crushing rate and dimensional stability coefficient of 2.853% and 3.274, respectively. Further verification experiments yielded a cottonseed crushing rate and dimensional stability coefficient of 2.888% and 3.282, respectively, with a maximum error of 3.85%, validating the model and optimized parameters. Therefore, strictly controlling seed cotton compression molding parameters was shown to reduce the cottonseed crushing rate and dimensional stability coefficient. These findings offer crucial theoretical insights for developing seed cotton compression processes and selecting parameters for cotton harvesting and packing devices.